Hydatid disease - (:unkn) unknown (Springer London, 2018)
Hydatid disease of the lung is a clinical entity since ancient times. It is a parasitic disease caused by Echinococcus granulosus, still endemic in different parts of the world particularly Mediterranean and Middle East countries. Pulmonary hydatid disease is more common in children compared to adults where hepatic hydatid disease is seen frequently. Laboratory diagnosis of the disease is supportive to clinical and radiological evaluation. Surgical treatment is advocated for the pulmonary hydatid disease. Open surgery, with low mortality and morbidity, is the standard approach. Video-assisted thoracoscopic surgery (VATS) is a novel approach for the resection of pulmonary hydatid cysts. Antihelminthic agents like albendazole and mebendazole are used for the medical treatment of the hydatid disease. The most common complications are pleural infection and prolonged air leak. This disease has a good prognosis with the help of appropriate surgery and medical treatment with low recurrence rates. © Springer-Verlag London Ltd., part of Springer Nature 2018.
Keywords: Aspiration; Capitonnage; Cystectomy; Echinococcus; Hydatid cysts; Hydatid disease; Prognosis; Pulmonary; Surgery; VATS